2018 IEEE International Conference on Fuzzy Systems (FUZZ-IEEE) 2018
DOI: 10.1109/fuzz-ieee.2018.8491507
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Computer Network Traffic Anomalies based on Eccentricity Analysis

Abstract: In this paper, we propose an approach to automatic detection of attacks on computer networks using data that combine the traffic generated with 'live' intra-cloud virtual-machine (VM) migration. The method used in this work is the recently introduced typicality and eccentricity data analytics (TEDA) framework. We compare the results of applying TEDA with the traditionally used methods such as statistical analysis, such as k-means clustering. One of the biggest challenges in computer network analysis using stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Besides, it has been shown that due to the recursion feature, TEDA is computationally more efficient and suitable for online and real-time applications. Other works in the literature also present similar results and conclusions [8], [10], [12], [27], [28]. The characteristics and advantages of the TEDA algorithm presented in these references have justified and motivated the choice of this algorithm, among several anomaly detection algorithms, for the implementation of the hardware architecture for streaming processes.…”
Section: Related Worksupporting
confidence: 62%
“…Besides, it has been shown that due to the recursion feature, TEDA is computationally more efficient and suitable for online and real-time applications. Other works in the literature also present similar results and conclusions [8], [10], [12], [27], [28]. The characteristics and advantages of the TEDA algorithm presented in these references have justified and motivated the choice of this algorithm, among several anomaly detection algorithms, for the implementation of the hardware architecture for streaming processes.…”
Section: Related Worksupporting
confidence: 62%
“…In the following subsections, the main mathematical concepts behind the methodology are shown and what makes it so flexible that it can be used for the development of a variety of algorithms, such as: anomalies and failure detection [ 49 ], image processing, clustering [ 50 , 51 ], classification [ 52 ], regression [ 53 ], forecast, control, filtering, big data [ 54 ], and traffic analysis [ 55 ], among others.…”
Section: Typicality and Eccentricity Data Analyticsmentioning
confidence: 99%
“…The paper published by [18] brings a study for anomaly detection in TCP / IP networks. The purpose of the paper is to detect computer network anomalies in the process of virtual machine (VM) live migration from local to cloud, by comparing this approach between TEDA, clustering K-Means, and static analysis.…”
Section: Related Workmentioning
confidence: 99%